The Impact of Hedonic Shopping Motivation, Live Streaming, and Flash Sales on Impulse Buying Behavior: A Study of Shopee E-Commerce Users in Semarang - Imamah, Istihabil; Zusrony, Edwin; Anzie, Luthfy Purnanta (SAFE-Network, 2025)
Hedonic shopping motivation, live streaming e-commerce, and flash sales together can lead to impulsive purchasing. This research focuses on the impacts of hedonic shopping and live stream flash sales on impulse buying on the Shopee e-commerce platform of the millennial population. This is primarily quantitative research, which exploits associative methodology based on primary data. The primary sample includes about 50 respondents, ranging from 18 to 35 years, and currently located in Semarang Regency, Indonesia. The 50 ‘target’ respondents were collected using purposive sampling techniques. The data were collected via online questionnaires based on a 5-Likert scale. Data were analysed using multiple linear regression and SmartPLS 4.1.1.2, from which the final thesis was confirmed. According to the outcomes of the study, the 4 hypotheses were accepted and confirmed. The data shows that the 3 chosen independent variables do, in fact, promote impulse buying on the Shopee platform. Then simultaneously, it was found that the hedonic shopping motivation, live streaming, and flash sale variables had an effect on impulse buying.